Photochemical Construction of Ni/CdS Double‐Walled Magnetic Hollow Microspheres with Simultaneously Enhanced Visible‐Light Photocatalytic Activity and Recyclability. Issue 8 (5th May 2021) - Zhong, Wenyu; Zhuang, Zefeng; Zhu, Zhimin; Zhou, Guangying; Zhu, Ximiao; Ma, Lijun; Xu, Bingjia; He, Guping; Gu, Fenglong; Sun, Fengqiang
Abstract: A new magnetic recyclable photocatalyst, consisting of a Ni/CdS double‐walled hollow microsphere based on a polymer microsphere template, was constructed entirely by use of a photochemical method. Under an ultraviolet lamp, the poly(styrene‐co‐acrylamide) microsphere template, the Ni magnetic wall and the CdS wall were fabricated in sequence in corresponding precursor solutions, and then the template was remove to obtain the structure. Both walls were mesoporous and molecularly passable, and their sequential assembly facilitated their respective roles in photocatalysis. The CdS wall was assembled on the outside of the structure to maximize exposure to its active sites, whereas the Ni wall was inside the structure and acted as a support, as a magnetic component, and also as an heterogeneous enhancer. When the structure was employed in photodegradation of methylene blue or in photocatalytic hydrogen evolution from water under visible light, it exhibited considerably enhanced activities, recyclability and stability compared to pure CdS hollow microspheres. Such a construction strategy using simply light energy is promising in the acquisition of high performance photocatalysts with recyclability or other functions. Abstract : Multipurpose material : A Ni/CdS double‐walled hollow microsphere magnetic recyclable photocatalyst based on a polymer microsphere template was constructed entirely through a photochemical route. When used in the photodegradation of methylene blue or in photocatalytic H2 evolution from water under visible light, it exhibited considerably enhanced activity, recyclability and stability compared to pure CdS hollow microspheres or template@Ni/CdS microspheres.